TRANSFORMASI TOKOH DALAM CERITA DEWI KEKAYI SEBAGAI HIPOGRAM CERPEN KEKAYI KARYA OKA RUSMINI (Character Transformation in the Dewi Kekayi Story as Hypogram of Short Story Kekayi by Oka Rusmini) - Alfian Rokhmansyah; Azizatur Rahma (SAWERIGADING, 2019)
This study aims to describe the transformation undergone by the characters in the story of Dewi Kekayi as a hypogram of the short story Kekayi (2017) by Oka Rusmini. Intertextual and hypogram theory are used as the basis of analysis. The research is a qualitative study with a structural approach. In addition, a text comparison method is also used to compare a short story text with its hypogram. Data analysis was done by comparing the motive of the story of Dewi Kekayi in the Ramayana epic as a hypogram and the short story Kekayi as a result of its transformation. The results of this study show that the story of Dewi Kekayi in the Ramayana epic was taken as the hypogram of the short story Kekayi, through the transformation of the story, especially with regard to the characters. In the transformation process, the author incorporates the original story (as a hypogram) into the new story, by adopting the characters in the story of Dewi Kekayi as figures in the short story Kekayi, including Kekayi, Bharata, Dasarata, Kekaya, and Rama. In addition, the author also deconstructs the personality of these characters leading to character trait discrepancies between the story of Dewi Kekayi story and the short story Kekayi.AbstrakPenelitian ini bertujuan untuk mendeskripsikan transformasi tokoh-tokoh dalam cerita Dewi Kekayi sebagai hipogram cerpen Kekayi (2017) karya Oka Rusmini. Teori intertekstual dan hipogram digunakan sebagai dasar dalam analisis. Penelitian ini merupakan penelitian kualitatif dengan pendekatan struktural. Selain itu juga digunakan metode perbandingan teks untuk membandingkan teks cerpen dengan hipogramnya. Analisis data dilakukan dengan membandingkan motif dari cerita Dewi Kekayi dalam epos Ramayana sebagai hipogram dan cerpen Kekayi sebagai hasil tranformasi. Hasil penelitian menunjukkan bahwa cerita Dewi Kekayi dalam epos Ramayana dijadikan hiprogram cerpen Kekayi oleh Oka Rusmini melalui transformasi cerita, khususnya pada tokohtokohnya. Dalam proses transformasi, pengarang mengembangkan cerita asal (sebagai hipogram) di dalam cerita baru, yaitu dengan menjadikan tokoh-tokoh dalam cerita Dewi Kekayi menjadi tokoh-tokoh dalam cerpen Kekayi, seperti tokoh Kekayi, Bharata, Dasarata, Kekaya, dan Rama.Selain itu, pengarang juga mendekonstruksi karakter tokoh-tokoh tersebut yang menyebabkan adanya kontradiksi sifat tokoh dalam cerita Dewi Kekayi dan cerpen Kekayi.